A novel fluorogenic probe for the investigation of free thiols: Application to kinetic measurements of acetylcholinesterase activity. (26th February 2016) - Mertens, Matthias D.; Bierwisch, Anne; Li, Tianwei; Gütschow, Michael; Thiermann, Horst; Wille, Timo; Elsinghorst, Paul W.
Graphical abstract: Highlights: A novel coumarin-derived turn-on probe for the detection of thiols with sufficient solubility in aqueous environments and excellent fluorescence characteristics. A fluorescence-based assay for acetylcholinesterase activity as an addition to the established Ellman methodology. Evaluation of the asymmetric sigmoidal product formation curves applying a three parameter Gompertz equation. Abstract: A novel coumarin-derived thiol probe, based on the thiol-promoted cleavage of a quenching 2, 4-dinitrobenzenesulfonyl group is described. The probe shows a sensitive fluorescence turn-on and sufficient solubility in aqueous environments. As a proof of concept, a new assay for AChE activity was developed as a useful addition to the established Ellman method. The observed reaction kinetics followed an asymmetric sigmoidal pattern and were successfully evaluated applying a three parameter Gompertz equation. Providing a linear relationship between the detected fluorescence formation curves and corresponding enzyme activities, this probe appears as a valuable tool for AChE activity measurements.